ANALISIS PENGARUH HARGA, KUALITAS PELAYANAN, DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN BINTANG BARBERSHOP DI TULUNGAGUNG 2021 - Ghozali, Rafiqul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is based on the rapid development of men's special hair cutting services, commonly called barbershops, which are growing quite rapidly. Developments in recent times. known for the increase in the number of men's haircut businesses more than ever before. Consumers are more able to choose a better haircut. Judging from the current situation, making men's barbershop entrepreneurs are required to choose a good strategy so that their customers are satisfied.      This study aims to (1) analyze the effect of price on customer satisfaction at Bintang Barbershop in Tulungagung Regency 2021 (2) analyze the effect of service quality on customer satisfaction at Bintang Barbershop in Tulungagung Regency 2021 (3) analyze the effect of store atmosphere on customer satisfaction at Bintang Barbershop in Tulungagung Regency 2021 (4) analyzing the effect of price, service quality, and store atmosphere on customer satisfaction at Bintang Barbershop in Tulungagung Regency 2021.